PERSPEKTIF GLOBAL PENYELESAIAN SENGKETA INVESTASI DI INDONESIA - Syaifuddin, Muhammad (Fakultas Syariah, 2011)
UUPM No.25/2007 is a yuridical consequence from World Trade Organization agreement (WTO) ratification. TRIMSs, aims to make investation law, including law on nvestation conflict solution hich is accordance with foreign investor tendency in global perspective namely; firts, the content has law characters which are definite, just, efficient; second, law spirit based directing the goverment and foreign investor to solve the investation conflict through national and international agreementÂ rather than court. The crisis of court institution in Indonesia must be solved by building court law system refering to pancasila as Indonesian investation law goal. That has been a requirement to form formal regulation for ideal investation conflict solution in local and international perspectivePembentukan UUPM No. 25/2007 adalah konsekwensi yuridis dari ratifikasi Perjanjian WTO. TRIMs, yang bertujuan menciptakan hukum investasi, termasuk hukum penyelesaian sengketa investasi, yang sesuai dengan kehendak investor asing dalam perspektif global, yaitu: pertama, mengandung karakter hukum yang berkepastian, berkeadilan, dan berefisiensi; dan kedua, berlandaskan spirit hukum yang mengarahkan pemerintah dan penanaman modal asing menyelesaikan sengketa investasi melalui arbitrase internasional daripada pengadilan bahkan arbitrase nasional di Indonesia. Krisis lembaga peradilan di Indonesia harus diselesaikan dengan cara membangun sistem hukum peradilan dengan mengacu pada Pancasila sebagai cita hukum investasi Indonesia. Hal tersebut adalahÂ suatu syarat bagi terbentuknya aturan hukum penyelesaian sengketa investasi yang serasi dalam perspektif global dan lokal (Indonesia).